The Eurasian Economic Union: Rethinking the Sovereign Path of Development - M. V. Myasnikovich; V. S. Kovalev (Евразийская интеграция: экономика, право, политика)
Aim. To reveal the main areas of work of the Eurasian Economic Commission and the Eurasian Economic Union (EAEU) in the near future.Tasks. Assess the processes of Eurasian integration both in a retrospective context and in terms of current geopolitical and geo-economic events.Methods. Statistical, comparative analysis, qualitative assessment, system approach, project approach.Results. The contours of the further development of the EAEU are outlined with an emphasis on the creation of a sovereign economic model, the improvement of the institutional and legal systems of the Union, and mutually beneficial cooperation with stable international partners.Conclusions. The history of the formation of the Eurasian Economic Union is connected with the successful overcoming of external and internal challenges, which clearly indicates its viability. In the current conditions, the EAEU needs to rethink the sovereign path of development, make adjustments to the logic and mechanisms for improving integration work, use the basic conditions to strengthen its own self-sufficiency.